Dogodek v mestu Gogi in model nove drame - Toporišič, Tomaž (Jezik in slovstvo, 2023)
The essay deals with one of the fundamental dilemmas that Slavko Grum’s plays, especially An Event in the Town of Goga, repeatedly raise, and it is connected with their multi-layered, almost paratactic character. It is precisely because of this characteristic that both literary and theatrical history oscillate between labels such as expressionism, decadence, symbolism, modernism, and so on. It attempts to show how the specifics of this new drama and the new concept of theatre and art in general are revealed precisely through the juxtaposition of An Event in the Town of Goga with the aesthetic revolutions of the historical and partly neo-avant-gardes, as well as of the modernism and neo-modernism of the twentieth century. In this way, when read and compared with contemporaries and successors, the (inter)media map of this highly interesting literary work emerges, which, like the Futurist, Dadaist, Absurdist, Surrealist and Expressionist syntheses, problematised the fundamental thematic preoccupation of the twentieth century: the crisis of the new-modern subject in the world proclaimed by Nietzsche with the absence of God. Grum’s oeuvre was thus, like that of the Expressionists and, at the same time, of Kosovel’s dramatic fragments, Mrak’s Obločnica, and Delak’s The Serpent in the Sky’s Dawn, heterogeneous. The various avant-garde tactics that developed simultaneously in European and American modernist drama and prose of the first half of the twentieth century entered into dialogue and interesting relationships with each other, and it is An Event in the Town of Goga that comes closest to some modernist or avant-garde procedures within Grum’s oeuvre.
Keywords: ekspresionizem; expresionism; Grum, Slavko; historical avant-garde; new drama; nova drama; simbolizem; Slovenian drama; slovenska dramatika; symbolism; zgodovinska avantgarda